2022
DOI: 10.3389/fpls.2022.1035851
|View full text |Cite
|
Sign up to set email alerts
|

A meta-quantitative trait loci analysis identified consensus genomic regions and candidate genes associated with grain yield in rice

Abstract: Improving grain yield potential in rice is an important step toward addressing global food security challenges. The meta-QTL analysis offers stable and robust QTLs irrespective of the genetic background of mapping populations and phenotype environment and effectively narrows confidence intervals (CI) for candidate gene (CG) mining and marker-assisted selection improvement. To achieve these aims, a comprehensive bibliographic search for grain yield traits (spikelet fertility, number of grains per panicle, panic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 130 publications
2
10
2
Order By: Relevance
“…The CI of 18 MQTL identified in this study was 3.44 times lower than that of the initial QTL studies indicating a possible close linkage of associated markers to the MQTL, thus enabling flexibility of introgressing MQTL in marker-assisted breeding. This finding is consistent with our previous report [ 39 ] and other studies in rice and wheat [ 30 , 57 , 58 ]. However, for individual MQTL, we found that MQTL3.2 had a large confidence interval (40.7 cM) although did not exceed the CI of the initial QTL (Supplementary Table 2 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The CI of 18 MQTL identified in this study was 3.44 times lower than that of the initial QTL studies indicating a possible close linkage of associated markers to the MQTL, thus enabling flexibility of introgressing MQTL in marker-assisted breeding. This finding is consistent with our previous report [ 39 ] and other studies in rice and wheat [ 30 , 57 , 58 ]. However, for individual MQTL, we found that MQTL3.2 had a large confidence interval (40.7 cM) although did not exceed the CI of the initial QTL (Supplementary Table 2 ).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, we conducted a meta-analysis of 120 previously reported QTL underlying submergence-related traits from 16 independent studies and discovered that these 120 QTL were unevenly spread across the rice chromosomes, with a large number of QTL located on chromosomes 7, 1, and 5 and the least QTL on chromosomes 4, 8, and 11 (Fig. 1 ) which agreed with our previous study [ 39 ] and studies conducted by Wu et al [ 56 ] and Khahani et al [ 37 ]. One of the interesting findings of this study is that the PVE by most of the initial QTL was low indicating that minor effect loci are at play in influencing rice submergence tolerance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the auxin response family members were found to be regulated by other transcription factors, such as the MYB transcription factor, the bHLH transcription factor, and the heat shock transcription factor (HSF) [ 59 , 60 , 61 ]. OsIAA3 is located in MQTL1.1, which refers to the traits of spikelet fertility, grain number per panicle and 1000-grain weight [ 62 ]. It was reported to regulate root growth and grain size in rice [ 63 , 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing yield potential has been a long-term objective in rice breeding and is imperative to overcome the global food crisis [ 4 9 ]. Rice yield is the most targeted complex trait that is a direct function of multiple factors including number and size of grains, productive tillers per plant, plant count per unit area, size of panicles and plant height [ 2 , 7 , 10 12 ] thus, the aforesaid component traits are prerequisite for achieving the desired yield in rice. This warrants the dissection of yield-related quantitative traits, discovery of the novel genetic factors and elucidate their molecular basis to meet the increased global rice demand.…”
Section: Introductionmentioning
confidence: 99%